Introduction and structure of the report: Global context and employment and social trends in the developing world. Issue 1 (23rd December 2014) - Kapsos, Steven
Abstract: This chapter provides an overview of global economic and labour market trends, through an analysis of trends in key indicators including GDP growth, employment, unemployment, labour productivity and working poverty, among others. It finds that the growing global jobs gap, characterised by particularly weak employment prospects for young people, is centred mainly in the developed economies, whereas the primary challenge facing many developing countries is widespread low‐productivity employment. The chapter provides evidence that growth in wage and salaried employment opportunities is positively associated with increased labour productivity and higher shares of workers attaining a middle class standard of living in the developing world.